2013
DOI: 10.5888/pcd10.120194
|View full text |Cite
|
Sign up to set email alerts
|

Leisure-Time Physical Activity and Its Association With Metabolic Risk Factors in Iranian Adults: Tehran Lipid and Glucose Study, 2005–2008

Abstract: We examined the association between leisure-time physical activity (LTPA) and metabolic syndrome (MetS) among 4,665 randomly selected adults who participated in the Tehran Lipid and Glucose Study, 2005–2008. Normal-weight participants with light LTPA had higher risk of low high-density lipoprotein cholesterol and elevated levels of triglycerides than those with vigorous LTPA. Overweight adults with moderate LTPA had higher risk of having elevated levels of fasting blood glucose than adults with vigorous LTPA a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 14 publications
(16 reference statements)
1
30
0
Order By: Relevance
“…However, we evaluated the association between H. pylori seropositivity and the cardiometabolic risk factors, paying particular attention to careful control for known risk factors and confounders including age, sex, smoking status, alcohol consumption, socioeconomic status, physical activity, and body mass index. Physical inactivity and obesity are established risk factors of metabolic syndrome and cardiovascular disease353637. The current study provides evidence that H. pylori infection is associated with dyslipidemia such as higher total cholesterol and LDL-C, as well as lower HDL-C, regardless of potential confounders and putative risk factors.…”
Section: Discussionmentioning
confidence: 53%
“…However, we evaluated the association between H. pylori seropositivity and the cardiometabolic risk factors, paying particular attention to careful control for known risk factors and confounders including age, sex, smoking status, alcohol consumption, socioeconomic status, physical activity, and body mass index. Physical inactivity and obesity are established risk factors of metabolic syndrome and cardiovascular disease353637. The current study provides evidence that H. pylori infection is associated with dyslipidemia such as higher total cholesterol and LDL-C, as well as lower HDL-C, regardless of potential confounders and putative risk factors.…”
Section: Discussionmentioning
confidence: 53%
“…Several cross-sectional studies in Western populations found that subjects who were more physically active had higher HDLC [33] and lower TG concentrations [34]. Findings from Korean adults [35] and Iranian adults [36] also showed that the amount and intensity of physical activity were positively associated with concentrations of TG or HDLC. One meta-analysis of randomized controlled trials reported that regular aerobic exercise significantly increased HDLC [37].…”
Section: Discussionmentioning
confidence: 88%
“…The role of LPA in MS is still inconclusive. One previous study identified that an inverse association between light LPA and MS in overweight adults, and light- or moderate-intensity LPA have higher risk of MS than vigorous-intensity LPA in normal-weight adults35. A meta-analysis with 10-years follow-up study reported that a 29 and 32% lower risk of MS in men and women associated with the highest levels of LPA, but a weaker association between MS and moderate LPA in men, compared with those in the lowest levels of LPA36.…”
Section: Discussionmentioning
confidence: 99%